Development of the Gnostic philosophy in its integration with the hermetic tradition - Natalia Skvorcova (Cхід, 2013)
This article discusses the integration of Gnosticism and Hermetic knowledge. Analyzed and found that the irrational and mystical knowledge of the Gnostic philosophy is intertwined with the wisdom of the Hermetic tradition. The basis of ontological and epistemological aspects of the process Cosmogenesis Gnostic concept forms the ancient teachings of Hermes Trisemgist.